Fungal infection aiming small bowel and multivisceral transplantation – Literature review - Massaia, Adriana Weinfeld; David, André Ibrahim; Gritti, Catiana Mitica; Silva, Ivan Leonardo Avelino França e; Abdala, Edson (Brazilian Journal of Transplantation, 2015)
The nature of infections after solid organ transplantation has changed significantly with the advent of potent immunosuppressive regimens, the routine use of antibiotic prophylaxis and the advancement of microbiological diagnostic techniques. New pathogens are being identified among this population, including several with significant antimicrobial resistance profile. Each type of graft has specific risks for infections, and both intestine and multivisceral transplants are important examples. However, the general infection patterns are similar to all solid organ transplants. Infections in these situations can be divided into categories: related to the donor, related to the receiver, infections acquired in the community and infections related to health care. The post-transplant chronology of infections is determined by the nature and intensity of individual epidemiological exposure and balance in the immunosuppression state. The scarcity of epidemiological studies on bowel and multivisceral post-transplant infections still maintain their understanding more as a state of the art than as a science. The purpose of this study is to describe the epidemiological data of the intestine and multivisceral post-transplant fungal infections. The most prevalent agents in the intestine transplants and multivisceral were: Candida spp. and Aspergillus spp. The main spots of infection were the surgical site, intra-abdominal, blood, central venous catheter, urinary and respiratory systems. The identified risk factors were: acute rejection, high dose of immunosuppression, use of invasive devices, extensive surgery and reoperation, contaminated graft, previous infection and hospitalized patients in the pre-transplant period.